Income and Asset Distribution in Thailand: An Analysis of Inequality Classified by Socioeconomic Class: การกระจายรายได้และทรัพย์สินในประเทศไทย: การวิเคราะห์ความเหลื่อมล้ำจำแนกตามชนชั้น - Hengpatana, Suwimon; Patmasiriwat, Direk; Ratchatapibhunphob, Pichit (Journal of Applied Economics and Management Strategy [eISSN 2985-1408], 2019)
บทคัดย่อ การศึกษาครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาสภาพเป็นจริง (Situational Analysis) ของการกระจายทรัพย์สินและรายได้โดยวิเคราะห์รายได้และการถือครองทรัพย์สินเป็นรายชนชั้น ใช้ทฤษฎีวงจรชีวิตและทฤษฎีทุนมนุษย์เป็นกรอบในการวิจัย ข้อมูลที่ใช้ในการวิจัยคือข้อมูลการสำรวจภาวะเศรษฐกิจและสังคมของครัวเรือน (Household Socio-Economic Survey) พ.ศ.2556 ที่สำรวจโดยสำนักงานสถิติแห่งชาติ ซึ่งการวิเคราะห์การกระจายทรัพย์สินและรายได้ ตลอดจนการวัดความเหลื่อมล้ำตามแหล่งรายได้ครัวเรือนและทรัพย์สินครัวเรือน ใช้ดัชนีจินี (Gini Coefficient) เป็นตัวชี้วัด รวมทั้งใช้เทคนิคแยกองค์ประกอบ (Gini Decomposition) เพื่อวิเคราะห์ความเหลื่อมล้ำระหว่างชั้นรายได้และภายในชั้นรายได้ ผลการวิจัยพบว่า เกษตรกร เกษตรผู้เช่า และแรงงานทั่วไปมีรายได้สัมพัทธ์ต่ำ ในขณะที่ผู้ประกอบการและนักวิชาชีพมีรายได้สัมพัทธ์สูงกว่าค่าเฉลี่ยดัชนีจินีของรายได้ต่อหัวในปี 2556 เท่ากับ 0.48 เมื่อวัดความเหลื่อมล้ำโดยแยกองค์ประกอบพบว่า ความเหลื่อมล้ำ ด้านรายได้ภายในชนชั้นเดียวกันร้อยละ 76 ในขณะที่ความแตกต่างระหว่างชนชั้นอธิบายได้ร้อยละ 24 ความเหลื่อมล้ำในการถือครองทรัพย์สินเท่ากับ 0.69 ทรัพย์สินประเภทประเภทบ้านที่ดินและอาคารพาณิชย์ มีสัดส่วนความสำคัญมากที่สุด แต่ทรัพย์สินทางการเงินก่อให้เกิดความเหลื่อมล้ำสูงที่สุดและหากครัวเรือน มีทรัพย์สินทางการเงินเพิ่มขึ้นจะทำให้เกิดความเหลื่อมล้ำเพิ่มขึ้น คำสำคัญ: การกระจายรายได้ ความเหลื่อมล้ำ ชนชั้นทางเศรษฐกิจและสังคม ABSTRACT The study aims to conduct a situational analysis of asset and income distribution through an analysis of asset ownership and income classified by class. The life cycle theory and human capital theory were the research frameworks applied to explain the experimental results. The data used in this study were the Household Socioeconomics Survey in 2013, conducted by the National Statistical Office. The analysis of income and asset distribution and inequality was explained using the Gini coefficient. The Gini decomposition technique was also applied to describe the inequality between and within socioeconomic classes, which were classified into five; namely, farmers, tenant farmers, general laborers, professionals, and entrepreneurs. The research findings revealed that farmers, tenant farmers, and general laborers had low relative income, whereas entrepreneurs and professionals had a higher relative income than the average. The Gini coefficient of income in 2013 was 0.48. The inequality divided by compositions revealed that 74 percent of the differences within the same class could be explained, whereas 26 percent of the differences between classes could be explained. The inequality in asset ownership reflected the ability to invest and the availability of risk management tools in the case of economic uncertainties, with a Gini coefficient of 0.65. The most important type of asset was houses/land/commercial buildings, but financial assets were seen to positively cause the most inequality among the three types of assets-meaning that if the household’s financial assets increase, it will cause greater disparity. Keywords: Income Distribution, Inequality, Socioeconomic Class